PEMBERIAN OBAT CACING RUTIN SEBAGAI UPAYA PENCEGAHAN STUNTING PADA ANAK USIA 4-5 TAHUN - Kurnia Sari Nia, Atika; Setianingsih, Setianingsih (Stikes Yarsi Mataram, 2024)
Stunting poses a public health issue in children aged 4-5 years. This research aims to evaluate the effectiveness of deworming as a preventive strategy for stunting in this age group. The community engagement method adopts a proactive approach, focusing on the positive impact of deworming on children's growth and development. Community service is conducted at PAUD Walisongo by administering deworming every 6 months, involving 15 children as participants. The activities in August 2023 were successful, with all children receiving deworming, reflecting the smooth implementation of the program. Height measurements indicate that all children fall within the normal category. The success of this community engagement serves as a foundation to expand the program to broader school and community environments, creating a positive impact on comprehensive stunting prevention. If continued, these steps can become an effective model for stunting prevention in various community contexts.